Early-Onset LBSL: How Severe Does It Get? - Steenweg, M. E.; van Berge, L.; van Berkel, C. G. M.; de Coo, I. F. M.; Temple, I. K.; Brockmann, K.; Mendonça, C. I. P.; Vojta, S.; Kolk, A.; Peck, D.; Carr, L.; Uziel, G.; Feigenbaum, A.; Blaser, S.; Scheper, G. C.; van der Knaap, M. S. (Neuropediatrics, 2012)
Aim Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) is known as a relatively mild leukoencephalopathy. We investigated the occurrence of severe variants of LBSL with extensive brain magnetic resonance imaging (MRI) abnormalities.Method MRIs of approximately 3,000 patients with an unknown leukoencephalopathy were retrospectively reviewed for extensive signal abnormalities of the cerebral and cerebellar white matter, posterior limb of the internal capsule, cerebellar peduncles, pyramids, and medial lemniscus. Clinical data were retrospectively collected.Results Eleven patients fulfilled the MRI criteria (six males); six had DARS2 mutations. Clinical and laboratory findings did not distinguish between patients with and without DARS2 mutations, but MRI did. Patients with DARS2 mutations more often had involvement of structures typically affected in LBSL, including decussatio of the medial lemniscus, anterior spinocerebellar tracts, and superior and inferior cerebellar peduncles. Also, involvement of the globus pallidus was associated with DARS2 mutations. Earliest disease onset was neonatal; earliest death at 20 months.Interpretation This study confirms the occurrence of early infantile, severe LBSL, extending the known phenotypic range of LBSL. Abnormality of specific brainstem tracts and cerebellar peduncles are MRI findings that point to the correct diagnosis.
Keywords: childhood white matter disorder; MRI pattern recognition; phenotypic variation